PENGARUH CUSTOMER EXPERIENCE DAN PERSEPSI HARGA TERHADAP MINAT BELI ULANG APLIKASI STREAMING DISNEY+ HOTSTAR - Rahmadhani, Novia Rizky; Wardhani, Nuruni Ika Kusuma (Unitri Press, 2024)
The research intends to explore as well as assess the impact of customer experience also price perception on repurchase interest for the Disney+ Hotstar streaming service. This study was conducted with 110 respondents, all of whom were Disney+ Hotstar customers living in Surabaya. The purposive sampling approach was employed, and the study was quantitative. The data will be measured and analyzed using SmartPLS. The study explains that: (1) Customer Experience has a significant impact on repurchase interest for the Disney+ Hotstar streaming service, and (2) Price Perception positively influences repurchase interest.